Two-dimensional thermal modelling with specular reflections in an experimental annealing furnace. Issue 1 (2nd January 2017) - Jadachowski, Lukas; Steinboeck, Andreas; Kugi, Andreas
ABSTRACT: A distributed-parameter model of the temperature in an experimental annealing device is developed. In particular, the two-dimensional spatial-temporal temperature evolution in a thin steel strip along its length and width is modelled during the heat-up process assuming temperature uniformity along the thickness. The model captures heat flows caused by thermal radiation in the considered partially specular enclosure, thermal conduction, internal forced convection, boundary heat flows, and in-domain heat sinks. Parameter identification is carried out based on the step response of the system measured by thermocouples and a temporarily installed infrared camera. For model verification, the simulated evolution of the temperature field in the specimen is compared with measurements. The relative accuracy of the proposed model is better than 4.4% of the maximum measured temperature.